Marriage Age Reform in Indonesia: Child Marriage Prevention Policies from the Perspective of Maqāṣid al-Sharīʿah - Firdaus, Firdaus; Habibulloh, Habibulloh; Hasibuan, Pendi; Rusyaida, Rusyaida (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
Despite legal reforms aimed at preventing child marriage in Indonesia, the practice continues to persist due to legal, institutional, and socio-cultural factors. Although Law No. 16 of 2019 equalizes the minimum marriage age at nineteen for both men and women, the existence of marriage dispensations and normative inconsistencies with the Compilation of Islamic Law create challenges for effective prevention. This study aims to analyze the reform of marriage age regulation and child marriage prevention policies in Indonesia through the perspective of maqāṣid al-sharīʿah, particularly the principle of Hifz al-nasl, which emphasizes the protection of lineage and the welfare of future generations. The research employs a normative juridical approach using doctrinal legal analysis through statutory and conceptual approaches. Primary legal materials consist of Marriage Law No. 1 of 1974, Law No. 16 of 2019, and the Compilation of Islamic Law, while secondary materials are derived from relevant academic literature. The findings indicate the minimum marriage age of nineteen is consistent with the principles of maqāṣid al-sharīʿah, particularly hifẓ al-nasl, as a preventive instrument to protect lineage and the well-being of future generations, although its effectiveness depends on consistent implementation and the substantive maturity of prospective spouses. Therefore, strengthening legal harmonization, regulating the use of marriage dispensations, and integrating community-based prevention policies are necessary to ensure that the objectives of Hifz al-nasl are effectively realized in contemporary child marriage prevention strategies.